Performance of FBK SiPMs coupled to PETA3 read-out ASIC for PET application - Piemonte, Claudio; Gola, Alberto; Tarolli, Alessandro; Fischer, Peter; Ritzert, Michael; Schulz, Volkmar; Solf, Torsten (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2013)
In this paper we show the energy and timing resolution performances of FBK SiPMs coupled to the PETA3 ASIC for PET application. We developed a measurement set-up to characterize single SiPMs coupled to scintillator exploiting the detector stack developed within the HYPERImage project. In this way we are able to characterize the combined SiPM/ASIC performance with the same signal chain (from the sensor to the ASIC board) used in the PET system. We show that using two scintillator detectors, composed of a 3×3×5mm3 LYSO crystal coupled to a 3×3mm2 SiPM, an intra-stack CRT of about 200ps FWHM can be obtained.
Available online 12 October 2012
Gesehen am 24.01.2022